Phylogeography and genetic structure of disjunct Salix arbutifolia populations in Japan. Issue 3 (26th February 2014) - Nagamitsu, Teruyoshi; Hoshikawa, Takeshi; Kawahara, Takayuki; Barkalov, Vyacheslav Yu.; Sabirov, Renat N.
Abstract: Disjunct geographic distributions of boreal plant species at the southern edges of their ranges are expected to result in low genetic diversity and high genetic differentiation in the disjunct populations. This prediction was tested in a riparian willow, Salix arbutifolia, distributed in the northeastern Eurasian continent and the Sakhalin, Hokkaido, and Honshu Islands, using chloroplast DNA haplotypes and nuclear microsatellite genotypes. Hokkaido and Honshu populations shared a chloroplast haplotype identical to a closely related species, S. cardiophylla . This haplotype was divergent from haplotypes in the Eurasian continent (Primorsky) and the Sakhalin Island. In the nuclear microsatellites, most Hokkaido populations were genetically closer to Primorsky populations than to Sakhalin populations in spite of the geographical vicinity between Sakhalin and Hokkaido. The unexpected genetic divergence between Sakhalin and Hokkaido implies a complicated history of migration and colonization. The most peripheral populations in Honshu had the lowest genetic diversity and were most differentiated from the others. Thus, low genetic diversity and high genetic differentiation at the range periphery suggest substantial effects of genetic drift on genetic structure in the disjunct populations of Salix arbutifolia at the southern edge of its range.